An assessment of property level rental price growth in Ireland - Slaymaker, Rachel; Kren, Janez; Devane, Katie (ESRI and RTB, 2024)
This report uses the first two years of newly collected annual registrations data from the RTB administrative tenancy registers to track individual rental properties over the period Q2 2022–Q1 2024. Using a large sample of 182,250 matched property pairs, for the first time, this report is able to examine how property level rents changed in Ireland over this period. This property level analysis provides complementary insights to those from the RTB/ESRI Rent Index indicators. While Rent Index measures provide the most accurate picture of how average rents are changing for new and existing tenancies, they are broad, market level indicators and do not track individual properties over time. They are designed to capture the impacts of both individual property rent changes and churn in the market. The focus of this report is solely on property level rent changes. The report addresses key research questions such as the magnitude of the average rental growth at the property level; the proportion of properties that saw no change in the rent; how rent changes differ between properties with ongoing tenancies (of at least one year in duration) compared to those that saw a change in tenants, i.e. where one lease ended and another began; and whether the patterns differ in areas designated as Rent Pressure Zones (RPZ) compared to non-RPZ areas. Key Findings: Rent levels grew by an average of 2.6% annually for the individual properties tracked in this study. 60% of all properties saw no increase in rent year-on-year. Landlords were more likely to raise rents between tenancies than during a tenancy, with 65% of ongoing tenancies experiencing no change in rent, compared with just 22% of properties where the tenants changed. Rent increases were lower for properties in RPZs. Rents for individual properties with ongoing tenants in Dublin grew on average by 1.3% annually to Q1 2024, by 1.4% in other RPZs but by 3.5% in non-RPZ areas. Rents for individual properties where tenants changed in Dublin grew on average by 2.8% annually to Q1 2024, by 5.2% in other RPZs but by 14.0% in non-RPZ areas. Properties in non-RPZs are more likely to see no change in rent each year, but when rent does increase, they are more likely to see significant hikes. Properties in RPZ areas are more likely to see moderate rent increases. 16.5% of existing tenants in non-RPZs experienced rent increases of 8% or more compared with 2.8% of tenants in Dublin and 4.8% in other RPZs over the two-year period. In non-RPZs, rent increased by 8% or more for 57% of properties where the tenants changed, compared to 8.5% in Dublin and 18.2% in other RPZs. In Dublin, 78.7% of properties where the tenants changed saw a rent increase of 4 per cent or below. In all counties, properties where the tenants changed saw higher rent increases. The highest rates seen were in Donegal (18.7%), Leitrim (18.3%) and Longford (19.3%). These were 6 times higher than seen in Dublin (3.1 per cent). Galway, Limerick and Waterford cities saw higher rates of rent increases above 8 per cent relative to Dublin and Cork, particularly where properties saw a change in tenants. More established RPZs (2016/17 designations) were more likely to see moderate price increases and fewer large rises than those designated in 2019/20. This suggests a possible higher level of non-compliance in more recently designated RPZs. While this study can tell us about the levels of rent increases observed for individual properties over this period, it cannot tell us if those rent increases complied with RPZ rules. Cumulative rent increases are permitted in RPZs where a landlord has not increased the rent in previous years, so increases >2% at a single point in time may legitimately occur. Further investigation is needed to understand the degree of cumulative increases (permitted) versus non-compliance.